Authentic Biology: Student-led research and discovery in schools. (25th January 2018) - Colthurst, David R.; Tuite, Mick F.
Abstract : Conducting cutting-edge biomedical research in schools and further education college laboratories has its challenges, but these are not insurmountable. In 2008, we established a successful cutting-edge research project into a debilitating human disease, in a secondary school environment. Here we provide a narrative describing the process behind the project, and then reflect not only on the process, but also on the benefits for school students, teachers and university researchers from engagement in such a collaborative project. We describe how, with significant financial input from a major biomedical charity, we were able to expand the initial project into Authentic Biology, a national programme of research in schools across the UK. Authentic Biology has resulted in six schools establishing their own novel research projects, mainly relating to human disease, and working in collaboration with their local university. Authentic Biology is a model for longterm school/college/university collaboration that is highly effective, productive and measurable through outcome. The challenge ahead is how to sustain the technical and financial support for such programmes.